A METHODOLOGY TO STUDY THE INFLUENCE OF THE KNOWLEDGE OF MATHEMATICAL DISCIPLINES FOR STUDYING SPECIAL DISCIPLINES - Gerasymenko, Petr; Khodakovskiy, Valentin; Verteshev, Sergey; Lyokhin, Sergey; Khvattcev, Alexander (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Professional training of students at the University should form the graduate's solid knowledge and ability to quickly master his often changing functional duties. To do this, the basic disci-plines of the engineer should be based on the fundamental disciplines of the first courses, which include, first of all, mathematics and physics. However, mathematical training of University students in the first years has become particularly difficult in recent years. It is known that today school graduates have a low level of exam scores in mathematics, which does not provide adequate assistance to successfully master not only higher mathematics at the University, but also special disciplines. In this regard, currently an urgent task is to study the levels of knowledge of special disciplines by students of technical universities, depending on the level of knowledge of mathematical disciplines. To ensure the quality of teaching mathematics at the University there are methodical systems of organization of level differentiation of training, which takes into account the initial level of pre-University training and corresponding to this level of the program of University mathematical training. However, their implementation is not very successful. The paper proposes a method of evaluation of the study of the connection of mathematical dis-ciplines with General scientific and special disciplines. Their establishment can allow to make necessary adjustments in their study for subsequent sets to the University.